Ethology of cross-breed cows milked in the presence or absence of calves - Vinícius Lopes da Silva; Fabiano Ferreira da Silva; Robério Rodrigues Silva; Fábio Andrade Teixeira; Lívia Santos Costa-Lopes; Danilo Ribeiro de Souza (Acta Scientiarum: Animal Sciences, 2014)
The behavior of crossbreed cows, milked in the presence or absence of their calves, was analyzed. The trial was conducted on the Dairy Cattle Sector of UESB School of Animal Science in Itapetinga BA Brazil. Twenty crossbreedHolsteinx Gir cows were distributed in a randomized block design with 10 replications for each treatment for the experimental period of 31 days, during lactation. Results were analyzed by nonparametric chi-square test at 5% significance, except the variables time at the milking sector and milk production which were evaluated by analysis of variance and F test at 5% probability. Although cows with the presence of calves during milking had higher reactivity, behavioral activities and more time in the milking sector, milk production was not affected.